Analgesics use for kidney failure - Rioko Kimiko Sakata; Marcelo Henrique Gomes Nunes (Revista Dor)
BACKGROUND AND OBJECTIVES:The use of drugs to treat renal failure has particularities due to pharmacokinetic changes present in such population. This study aimed at supplying subsidies for a rational choice of analgesics to be used in patients with renal failure.CONTENTS:Information is provided about pain prevalence and etiology in renal failure patients. In addition, the use of anti-inflammatory drugs, opioid analgesics and adjuvant drugs for pain management is addressed.CONCLUSION:Adjusting pharmacological therapy to renal function impairment may provide effective treatment with less adverse effects.